Association Between Food Content Preferences on Social Media and Risky Eating Behaviors Among High School Students - Mike Fitria; Lubis, Zulhaida; Lubis, Namora Lumongga (Jurnal Kesehatan Prima, 2025)
Most adolescents are prone to risky eating behaviors, which are unhealthy and nutritionally imbalanced. Dietary behaviors and eating habits are still developing in adolescents; therefore, it is important to encourage them against adopting risky eating behaviors to prevent various future health problems, such as obesity, diabetes mellitus, and coronary heart disease. This study aims to analyze the association between preference towards food content on social media and the level of risky eating behavior among high school students in Medan. The sample size in this cross-sectional study was 334 high school students selected by simple random sampling. Data were then analyzed using the chi-square test. The results indicated that there was a significant association between preference toward food content on social media and risky eating behavior among high school students in Medan (p<0.001). High school students with negative preferences, who prefer to watch and follow popular or trending but unhealthy food content on social media, had a 2.188 (95% CI: 1.703–2.811) times greater risk of adopting more severe levels of risky eating behavior than those with positive preferences. The health department is suggested to collaborate with schools and parents in implementing social media literacy programs aimed at educating high school students to be more discerning in watching food content on social media while still considering nutritional value and learning about the impact of their preferred foods.